REM sleep behavior disorder and Prodromal Parkinson’s Disease in patients with Essential Tremor - Paulo Bugalho; Bruna Meira; André Pinho; Rita Ventura; Marta Magriço; Miguel Serôdio; Danna Krupka; Vítor Mendes Ferreira (Sleep Medicine: X)
Several studies suggested the presence of non-motor symptoms in Essential Tremor (ET), including REM sleep behavioral disorder (RBD). RBD is an essential criterion for Prodromal Parkinson's Disease (PPD), suggesting a link between ET and PD. Our objective was to assess the prevalence and features of ET patients with RBD and PDD.RBD was diagnosed by questionnaire screening, followed by polysomnography. PPD risk factors and prodromic markers were assessed with a structured protocol. Patients were characterized regarding tremor features. ET patients with RBD (ET-RBD) and PPD (ET-PPD) were compared to patients without RBD (ET-nonRBD) and without PPD (ET-nonPPD), respectively. ET-RBD patients were also compared with a group of isolated RBD (iRBD) regarding PPD features.We assessed a total of 64 ET patients. Five (8.3 %) and 4 (6.3 %) had criteria for RBD and PPD, respectively. ET-RBD patients did not differ from ET-nonRBD except for a higher prevalence of PPD. There were no significant differences between ET-RBD and iRBD (n = 12) groups. ET-PPD had a higher prevalence of positive DaT-Scans and RBD compared to ET-nonPPD. Three ET-RBD patients had PPD and 3 ET-PPD had RBD.Both RBD and PPD are more frequent in ET patients than in general aged population but not related with specific tremor features. ET-RBD patients did not differ significantly from iRBD patients, a group prone to develop PD. These data suggest a link between ET and PD and are in accordance with studies showing an increase incidence of lewy-body pathology and PD in ET populations.